Inflation, dark energy, and dark matter - Kalita, Ranku (International Journal of Advanced Astronomy, 2017)
Inflation leads to â„¦ = 1 for the big bang universe, and which is indeed observed. However, the presence of two mysterious constituents in the big bang universe â€“ dark energy and dark matter â€“ also produces â„¦ = 1. This paper utilizes propositions about the nature of dark energy and dark matter to trace their origins to the contents of the inflationary universe.Â